Pemikiran Pendidikan Akhlak Al-Syaibany dan Relevansinya Di Era Modern - Mukminin, Amir; Wahyuni, Ruslina Dwi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2023)
This research aims to discuss Al-Syaibany's moral education thoughts and their relevance in the modern era. The discussion approach uses qualitative methods and literature studies. Based on the results of the discussion, Al-Syaibany's basic moral principles consist of 6 principles. First, believe in the importance of morals in life. Second, believe that morals are deep attitudes in the soul. Third, believe that morals are achieving happiness in this world and the hereafter for individuals and society. Fourth, believe that the goal of morals is to achieve happiness in this world and the hereafter for individuals and society. Fifth, believe that morals are in accordance with human nature. Sixth, believe that moral theory is not perfect unless it determines some of the basic concepts such as moral conscience, moral compulsion, moral law, moral responsibility, and moral reward. Of relevance, moral education is very important to be used as the main instrument in determining policies at all levels of education in various educational institutions.